Simultaneous Quantification of the Acetylome and Succinylome by 'One‐Pot' Affinity Enrichment. Issue 17 (19th August 2018) - Basisty, Nathan; Meyer, Jesse G; Wei, Lei; Gibson, Bradford W; Schilling, Birgit
Abstract: Protein posttranslational modifications (PTMs) are of increasing interest in biomedical research, yet studies rarely examine more than one PTM. One barrier to multi‐PTM studies is the time cost for both sample preparation and data acquisition, which scale linearly with the number of modifications. The most prohibitive requirement is often the need for large amounts of sample, which must be increased proportionally with the number of PTM enrichment steps. Here, a streamlined, quantitative label‐free proteomic workflow—"one‐pot" PTM enrichment—that enables comprehensive identification and quantification of peptides containing acetylated and succinylated lysine residues from a single sample containing as little as 1 mg mitochondria protein is described. Coupled with a label‐free, data‐independent acquisition (DIA), 2235 acetylated and 2173 succinylated peptides with the one‐pot method are identified and quantified and peak areas are shown to be highly correlated between the one‐pot and traditional single‐PTM enrichments. The 'one‐pot' method makes possible detection of multiple PTMs occurring on the same peptide, and it is shown that it can be used to make unique biological insights into PTM crosstalk. Compared to single‐PTM enrichments, the one‐pot workflow has equivalent reproducibility and enables direct assessment of PTM crosstalk from biological samples in less time from less tissue.